Precision Livestock Farming: An international review of scientific and commercial aspects - Banhazi, Thomas M.; Lehr, H; Black, J L; Crabtree, H; Schofield, P; Tscharke, M; Berckmans, D (International Journal of Agricultural and Biological Engineering, 2012)
Precision Livestock Farming (PLF) is potentially one of the most powerful developments amongst a number of interesting new and upcoming technologies that have the potential to revolutionise the livestock farming industries. If properly implemented, PLF or Smart Farming could (1) improve or at least objectively document animal welfare on farms; (2) reduce greenhouse gas (GHG) emission and improve environmental performance of farms; (3) facilitate product segmentation and better marketing of livestock products; (4) reduce illegal trading of livestock products; and (5) improve the economic stability of rural areas. However, there are only a few examples of successful commercialisation of PLF technologies introduced by a small number of commercial companies which are actively involved in the PLF commercialisation process. To ensure that the potential of PLF is taken to the industry, it is recommended to: (1) establish a new service industry; (2) verify, demonstrate and publicise the benefits of PLF; (3) better coordinate the efforts of different industry and academic organisations interested in the development and implementation of PLF technologies on farms; and (4) encourage the commercial sectors to assist with professionally managed product development.Keywords: Precision Livestock Farming(PLF), smart farming, commercialisation, scientific issue, animal welfare, efficiencyDOI: 10.3965/j.ijabe.20120503.001Citation: Banhazi T M, Lehr H, Black J L, Crabtree H, Schofield P, Tscharke M, et al. Precision Livestock Farming: An international review of scientific and commercial aspects. Int J Agric & Biol Eng, 2012; 5(3): 1